2013
DOI: 10.2355/isijinternational.53.152
|View full text |Cite
|
Sign up to set email alerts
|

Recrystallization Behavior of IF Steel Sheets Immediately after Hot-rolling in Ferrite Region

Abstract: It is known that high r-value hot-rolled steel sheets can be produced by hot rolling in the ferrite region with lubrication, whereas dynamic recovery easily occurs during ferritic rolling, in which texture formation is quite different from that in cold rolling, when the quantity of recovery increases. In this study, one pass hot rolling in the ferrite region was conducted at higher temperatures, using various rolling temperatures and rolling reductions, with two types of ULC steels, 0.016% Nb and 0.023% Ti, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
(15 reference statements)
1
3
0
Order By: Relevance
“…Urabe et al performed cold-rolling reductions of 0.080/ 0Ti-0.01%Nb IF steel until reductions of 70% and 85% were achieved, following which the deformed samples were annealed at 720°C for various durations [37]. e authors reported a trend similar to that observed in the present work, i.e., the hardness diminished as recrystallisation progressed; despite this, the deformation percent was higher in the Okuda et al carried out hot-rolling in the ferrite region at various rolling temperatures and to achieve di erent rolling reductions [38]. is process was applied to IF steel with a composition of 0.016% Nb and 0.023% Ti.…”
Section: Variations In Hardness From Deformed To Recrystallisedsupporting
confidence: 83%
See 1 more Smart Citation
“…Urabe et al performed cold-rolling reductions of 0.080/ 0Ti-0.01%Nb IF steel until reductions of 70% and 85% were achieved, following which the deformed samples were annealed at 720°C for various durations [37]. e authors reported a trend similar to that observed in the present work, i.e., the hardness diminished as recrystallisation progressed; despite this, the deformation percent was higher in the Okuda et al carried out hot-rolling in the ferrite region at various rolling temperatures and to achieve di erent rolling reductions [38]. is process was applied to IF steel with a composition of 0.016% Nb and 0.023% Ti.…”
Section: Variations In Hardness From Deformed To Recrystallisedsupporting
confidence: 83%
“…In the present work, the values of hardness measured at 0 s, 60 s, and 120 s of annealing were superior, in the range 152-186 HV. is behaviour is certainly because the present work entailed static recovery, whereas the cited work entailed a process of dynamic recovery; the former proceeds at a lower rate than the latter [38].…”
Section: Variations In Hardness From Deformed To Recrystallisedmentioning
confidence: 75%
“…The finishing rolling temperature range of ferrite rolled sheet was ferrite single phase region, and the deformation rate was high in CSP process. It was difficult for ferrite to recrystallize when the low carbon steel was deformed under these conditions . As shown in Figure , The grain will be elongated along the direction of deformation, which leads to a significant increase of the ferrite grain size.…”
Section: Discussionmentioning
confidence: 99%
“…Kiet Tieu researched the lubrication technology of ferritic rolling process [11,12]. Kaneharu OKUDA investigated the recrystallization behavior of Nb-IF and Ti-IF steel sheets immediately after hot-rolling in ferrite region [13]. Humphreys investigated the ferritic rolling behavior of low carbon steel [14].…”
Section: Introductionmentioning
confidence: 99%